2021
DOI: 10.1186/s42077-021-00133-x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled study comparing intravenous dexmedetomidine plus ketamine combination with intravenous dexmedetomidine alone for awake fibreoptic nasotracheal intubation

Abstract: Background The purpose of this study was to compare the efficacy and safety of dexmedetomidine versus dexmedetomidine and ketamine for sedation during awake fibreoptic intubation (FOI) in patients posted for elective surgeries. Ninety-eight American Society of Anesthesiologists Physical Status (ASA-PS) I–II patients with difficult airway and scheduled for elective surgeries were enrolled in this study after institutional ethics committee approval. Patients were randomly allocated into 2 groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 12 It is usually performed while the patient is conscious and able to maintain airway reflexes. 14 , 15 As recommended by the 2022 ASA Practice Guidelines for Management of the Difficult Airway 12 , nasal AFOI was performed in this case rather than a surgical tracheostomy owing to the anatomical and clinical presentation of the base of tongue mass. 13 , 15 Ideally, a reinforced tracheal tube should be used to prevent compression by the retractor or robotic arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 It is usually performed while the patient is conscious and able to maintain airway reflexes. 14 , 15 As recommended by the 2022 ASA Practice Guidelines for Management of the Difficult Airway 12 , nasal AFOI was performed in this case rather than a surgical tracheostomy owing to the anatomical and clinical presentation of the base of tongue mass. 13 , 15 Ideally, a reinforced tracheal tube should be used to prevent compression by the retractor or robotic arms.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 As recommended by the 2022 ASA Practice Guidelines for Management of the Difficult Airway 12 , nasal AFOI was performed in this case rather than a surgical tracheostomy owing to the anatomical and clinical presentation of the base of tongue mass. 13 , 15 Ideally, a reinforced tracheal tube should be used to prevent compression by the retractor or robotic arms. 11 However, to facilitate TORS procedure, it requires the head to be in full extension and the length of the tracheal tube needs to be appropriately chosen to allow for this head extension 16 , hence the use of nasal RAE.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 describes recent comparative evidence of various methods of intravenous sedation for awake intubation [24,25 ▪ ,26,27,28 ▪▪ ,29–33]. Many studies assessed the efficacy of intravenous dexmedetomidine in the setting of awake intubation, and revealed that it often led to shorter time to intubation, higher patient satisfaction, greater hemodynamic stability, fewer incidences of oxygen desaturation and/or hypercarbia postintubation, decreased coughing, and better intubating conditions [24,25 ▪ ,26,27,28 ▪▪ ,29–33]. Furthermore, Jamgade et al [25 ▪ ] assessed the effect of the addition of intravenous ketamine to dexmedetomidine, and found that it led to shorter intubation times compared with dexmedetomidine alone, while better preserving hemodynamic stability.…”
Section: Sedation Methodsmentioning
confidence: 99%
“…Though not every combination of sedatives has been assessed in a randomized trial, it is likely that a balanced technique with multiple sedatives can provide the benefits of each sedative, while minimizing the risks associated with each medication. Table 2 describes recent comparative evidence of various methods of intravenous sedation for awake intubation [24,25 ▪ ,26,27,28 ▪▪ ,29–33]. Many studies assessed the efficacy of intravenous dexmedetomidine in the setting of awake intubation, and revealed that it often led to shorter time to intubation, higher patient satisfaction, greater hemodynamic stability, fewer incidences of oxygen desaturation and/or hypercarbia postintubation, decreased coughing, and better intubating conditions [24,25 ▪ ,26,27,28 ▪▪ ,29–33].…”
Section: Sedation Methodsmentioning
confidence: 99%
See 1 more Smart Citation